Effect of PyC Inner Coating on Preparation of 3C-SiC Coating on Quartz Glass by Chemical Vapor Reaction - Wu, Jian; Qian, Shengteng; Huo, Tongguo; Zheng, Jianxin; Zhang, Pinlong; Dai, Yu; Geng, Dongsheng (Frontiers in Materials, 2022)
The cubic polycrystal of SiC (3C-SiC) coating on the quart glass (QG) surface was successfully prepared via a two-step chemical vapor deposition (CVD) by introducing a thin PyC coating as a buffer layer. Through combining the intake system of CVD PyC and CVD SiC, the SiC/PyC composite coating can be in-situ prepared on the QG without halfway in-and-out chamber. The results showed that the SiC/PyC composite coating possesses highly uniform, dense, and continuous features, while the pure SiC coating exhibits many cracks, implying that the internal stress between the SiC coating and the QG can be relieved by adding the PyC buffer coating. The average hardness of the SiC/PyC/QG is measured to be 46.8 GPa, and its calculated modulus is 416.3 GPa by using a nanoindentation technique. Compared to the pure QG, the friction coefficient of the SiC/PyC/QG is slightly increased to 1.47 versus 1.45. Moreover, the SiC/PyC/QG displays the excellent anti-acid corrosion in the 5%HF and 5%HCl mixed solution with the weight loss of about 33% lower than the pure QG after 8 h acid test at 80℃.